Strategies for global R&D - Chiesa, Vittorio
Vittorio Chiesa explains what it means for an international company to be managed as a coordinated network emphasizing innovation and R&D/technology.
The coordinated network company places a priority on innovation networks and the management of R&D/technology as a key factor in worldwide innovation.
Increasingly, multinational enterprises face simultaneous pressures for global integration and local responsiveness. Both management theorists and managers believe that, to respond to this challenge, the international company should be managed as a coordinated network. This model insists on the relevance of an international innovation network, on global management of technology, and on the capability to leverage the "best" elements of each location to global benefit. This implies that companies disperse their R&D facilities in different countries to a much larger extent than in the past. An R&D structure should be designed to fulfill three main tasks : constituent technology development, product development, and technical support to other functions. The drivers of internationalization, the locational determinants, and the management processes are unique to each task.
Keywords: Global R&D.